The Usefulness of IOLMaster™ from the Point of Refractive Error after Simultaneous Vitrectomy and Cataract Surgery - Sato, Yu; Sakurai, Yukari; Kanai, Yukari; Hori, Sadao; Shikama, Satoko; Aizawa, Minami (JAPANESE ORTHOPTIC JOURNAL, 2008)
Purpose: To study the usefulness of the IOLMaster™, a non-contact type optical device, in measuring the axial lengths of patients before and after simultaneous cataract and vitreous surgery (simultaneous surgery). Subjects and Methods: The study was conducted on 19 eyes of 18 patients who underwent the routine simultaneous surgery from September 2005 to September 2007. All patients had normal axial lengths ranging from 22.0 to less than 24.5mm, and were followed up for 2 month and more after the surgery. The control group consisted of 81 eyes of 69 patients who underwent cataract surgery alone (simple procedure). The axial length measurements were obtained on the same day with the IOLMasterTM and the conventional ultrasound A-mode method (A-mode). We used the SRK-T formula in order to calculate the IOL power. As A-constant value, personal A-constant value (118.6) of the normal axial length group was used for the A-mode, while the value (118.9) obtained from the data published on the web site was used for the IOLMaster™. The refractive error after the triple procedure surgery was compared between the IOLMaster™ and the A-mode. Results: The actual postoperative refractive error shifted more significantly towards myopia in A-mode than in IOLMaster™ (p<0.01, t-test). Even in subjects with cystoid macular edema (CME) or serosity retinal detachment (SRD), the postoperative refractive error shifted more significantly towards myopia in A-mode than in the IOLMaster™ (p<0.05, t-test). Conclusion: The postoperative myopic shift was less in the IOLMaster™ than in the A-mode. We conclude that the IOLMaster™ is a useful device for intraocular lens power calculation not only in simple procedure but also in simultaneous surgery because the condition of macular does not influence the axial length readings unless the lesion involves the retinal pigment epithelium.